Pengaruh Kompetensi Manajerial, Supervisi Akademik Kepala Sekolah Dan Budaya Sekolah Terhadap Kinerja Guru Dalam Implementasi Kurikulum Merdeka Di TK Negeri Kabupaten Bireuen - Naina Munacia; Saiful Bahri; Alfi Syahrin (Journal on Education, 2025)
The objectives of this research are: 1) To analyze the influence of managerial competence on teacher performance; 2) To analyze the influence of Academic Supervision on Teacher Performance; 3) To analyze the influence of school culture on teacher performance; 4) To analyze the influence of Managerial Competence, Academic Supervision and School Culture simultaneously on teacher performance in implementing the independent curriculum. This research method uses quantitative research methods, with data collected through questionnaires distributed to 120 research samples from 172 research populations. The results of this research; 1) managerial competence has a positive and significant influence on teacher performance by 32%, 2) academic supervision has a positive and significant influence on teacher performance by 7%, 3) school culture has a positive and significant influence on teacher performance by 32%.